Ergonomics and performance of using prismatic loupes in simulated surgical tasks among surgeons – a randomized controlled, cross-over trial - Fan, Xuelong; Yang, Liyun; Young, Nathalie; Kaner, Ilayda; Kjellman, Magnus; Forsman, Mikael (Frontiers in Public Health, 2024)
Introduction Recently developed prismatic loupes may mitigate the high physical workload and risk of neck disorders associated with traditional surgical loupes among surgeons. However, research in this area, particularly among surgeons, is sparse. This study examines the impact of prismatic loupes on surgeons’ physical workload, musculoskeletal discomfort, and performance during simulated surgical tasks. Materials and methods Nineteen out of twenty recruited surgeons performed three tasks in a fixed-order with their own loupes and both low-tilt (LT) and high-tilt (HT) prismatic loupes, in a randomized order. The primary outcomes were the median inclination angles and velocities of the head, trunk, and upper arms, along with the median muscle activity of the cervical erector spinae (CES), upper trapezius (UT), and lumbar erector spinae (LES) for each pair of loupes. The secondary outcomes included performance (completion time and errors), perceived body-part discomfort, and subjective evaluation of the three pairs of loupes. Results Using prismatic loupes, either LT or HT, compared with the surgeons’ own loupes yielded lower head inclinations (all p < 0.001), lower neck muscle activity (all p < 0.05), and lower neck discomfort in indirect comparisons (p < 0.01) with no significant difference in surgical errors (p = 0.628). However, HT loupes resulted in a longer task completion time in two tasks (p < 0.001). Most surgeons preferred LT loupes (N = 12) for their comfort and visual functions. Discussion The results indicate that prismatic loupes can reduce physical workload in the neck during simulated surgical task, with no significant difference in surgical errors. Future studies are needed to investigate the long-term effects of prismatic loupes among surgeons.